Proceedings of the Creative Construction E-Conference 2020 2020
DOI: 10.3311/ccc2020-003
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Digital Twin Model for Real-Time Assessment of Collision Hazards

Abstract: The AEC industry is nowadays one of the most hazardous industries in the world. The construction sector employees about 7% of the world's work force but is responsible for 30-40% of fatalities. As statistics demonstrate, interferences between workers-on-foot and moving vehicles have caused several injuries and fatalities over the years. Despite safety organizational measures, passive safety devices imposed by regulations and efforts from training procedures, scarce improvements have been recorded. Recent resea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…Maintaining the appropriate level of situation awareness, which is critical to safety, is therefore a challenge [ 11 ]. Within the context just described, collision accidents involving operators and moving construction vehicles are one of the main safety issues in construction workplaces, being one of the leading causes of non-fatal accidents and one of the most frequent causes of death on construction sites internationally [ 12 , 13 , 14 , 15 , 16 ]. The dynamic characteristics of construction site activities may be the cause of collision accidents, with construction resources often moving in situations of excessive proximity [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Maintaining the appropriate level of situation awareness, which is critical to safety, is therefore a challenge [ 11 ]. Within the context just described, collision accidents involving operators and moving construction vehicles are one of the main safety issues in construction workplaces, being one of the leading causes of non-fatal accidents and one of the most frequent causes of death on construction sites internationally [ 12 , 13 , 14 , 15 , 16 ]. The dynamic characteristics of construction site activities may be the cause of collision accidents, with construction resources often moving in situations of excessive proximity [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Inadequate analysis of spatial interferences in the design of construction site layouts often results in construction site spaces that are, at least temporarily, inadequate for the safe conduct of operations [ 17 , 18 ]. In addition, other factors can be identified that increase the likelihood of workers becoming victims of collision accidents: for example, the possible loss of concentration in performing daily activities due to fatigue and repetitive tasks, and the reduced visibility of construction vehicle operators due to blind spots [ 8 , 12 , 13 , 14 , 15 , 16 ]. Statistics, in fact, often highlight how collision fatalities can be caused by the failure of the operator to check the position of workers in the manoeuvring area, leaving workers undetected in blind spots or too close to moving vehicles [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation